Влияние кремниевой подложки на пробивное напряжение разветвленного n++–p+-перехода - Sidorenko, V. P.; Kizyak, A. Yu.; Nikolaenko, Yu. E. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper examines the influence of microdefects, as well as oxygen and carbon impurities in the silicon substrate, on the breakdown voltage of an uncontrolled n++–p+ junction. The mechanism of oxygen impurity impact on the type of breakdown is briefly discussed. Practical applications of the results in VLSI manufacturing technology are considered.